1998
DOI: 10.1207/s15327108ijap0804_1
|View full text |Cite
|
Sign up to set email alerts
|

Elevation-Dependent Symptom, Mood, and Performance Changes Produced by Exposure to Hypobaric Hypoxia

Abstract: Altitude exposures above 3,000 m produce changes in symptoms, moods, and cognitive/motor performance of unacclimatized individuals and should produce graded effects on these parameters as elevation and duration are increased. This study examined effects on these parameters as a function of altitude level and duration of exposure by administering standardized tests from 1 to 3 times to 23 males in an altitude chamber during 4.5-hour exposures to 3 levels of hypobaric hypoxia: 500 m, 4,200 m, and 4,700 m. Exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 12 publications
6
69
0
Order By: Relevance
“…This finding suggests that though there are temporal inductions of anxiety-like behavior in rats exposed to HH for 7 days, it does not lead to induction of depressive disorder on prolonged exposure. Supporting the present observation, previous reports showed that mood state alteration on exposure to HH depends on the altitude and is transient in nature [44].…”
supporting
confidence: 91%
“…This finding suggests that though there are temporal inductions of anxiety-like behavior in rats exposed to HH for 7 days, it does not lead to induction of depressive disorder on prolonged exposure. Supporting the present observation, previous reports showed that mood state alteration on exposure to HH depends on the altitude and is transient in nature [44].…”
supporting
confidence: 91%
“…More adverse changes were noted with longer durations after ascent, especially for 4,700 m simulated altitude. This study, like Banderet's earlier study, 26 demonstrated that moods are significantly altered after only a few hours of exposure to simulated altitude; effects increase (incidence and magnitude) when testing is conducted at 4,700 compared with 4,200 m. 30 In still another study, Shukitt-Hale, Rauch, and Foutch 31 evaluated self-rated symptoms and mood states during a climb of Mount Sanford in Alaska. Self-rated moods and symptoms were determined with the Profile of Mood States and the Environmental Symptoms Questionnaire.…”
Section: Mood Statessupporting
confidence: 50%
“…29 In another study, mood states were evaluated using the Profile of Mood States and the Clyde Mood Scale during a 4.5-hour exposure to a simulated altitude of 4,200 or 4,700 m to examine changes as a function of altitude level and duration of exposure. 30 Effects of 4,700 m altitude were seen for 75% of mood factors (friendliness, sleepiness, dizziness, hostility, depression, anxiety, confusion, fatigue, tension, anger, and vigor), while the effects of 4,200 m altitude were seen for only 25% of mood factors (sleepiness, dizziness, tension, and confusion). More adverse changes were noted with longer durations after ascent, especially for 4,700 m simulated altitude.…”
Section: Mood Statesmentioning
confidence: 98%
See 1 more Smart Citation
“…Despite the strong association between suicide and altitude, other factors may be responsible for this association that are directly related to high altitude per se, for example, low barometric pressure (Shukitt et al, 1998). Many demographic, psychiatric, and sociocultural factors are associated with suicide, and association between high altitude and suicide is speculative.…”
Section: Us Suicide Rates Increase With Altitudementioning
confidence: 99%